Application of Problem Based Learning Model to Improve Learning Outcomes of Al-Qur'an and Hadith, Generous and Miserly Materials at Madrasah Tsanawiyah - Zulfa, Siti (Research Journal on Teacher Professional Development, 2024)
This research aims to improve the learning outcomes of the Qur'an, Hadith, generous and miserly material at Madrasah Tsanawiyah. The research discussed that the low learning outcomes of students in the subject of Al-Qur'an Hadith, especially in the material about achieving the pleasure of Allah SWT through generosity and avoiding miserliness, are the main concerns. This phenomenon is caused by the conventional learning method that is often used by teachers, namely the lecture method, which tends to be less interactive and does not involve reciprocity between teachers and students. To overcome this problem, the author applies the Problem Based Learning model in classroom action research conducted in class VII B MTs Darul Hikam Kalirejo Undaan Kudus. This model is designed to increase students' enthusiasm and motivation to learn, which has been proven to be effective in this study. The results of the implementation of the Problem Based Learning model showed a significant increase in students' learning activities and their learning outcomes. In the first cycle, the learning completion rate reached 57.14%, then increased to 67.86% in the second cycle, and reached 89.29% in the third cycle. This increase in learning completeness shows that the Problem Based Learning model not only increases students' motivation and enthusiasm, but also improves their learning outcomes in the Qur'an Hadith material. Thus, the use of the Problem Based Learning model has proven to be effective in improving student learning outcomes in the subject of Al-Qur'an Hadith in class VII B MTs Darul Hikam.